Pseudorevertants of a lac promoter mutation reveal overlapping nascent promoters. - Karls, R (Nucleic Acids Res, 1989)
Four pseudorevertants of a -10 region lacP mutation were isolated. Three of these mutations were found to activate nascent promoters. These mutations were: a -2 G/C----A/T change (-2A) promoting transcription at position +11, a +1 A/T----T/A change (+1T) promoting transcription initiation at position +13, and a +10 C/G----A/T change (+10A) promoting transcription initiation at a complex series of positions. The fourth mutation [a -12 T/A----A/T change (-12A)] promotes transcription initiation at -1. The promoters activated by mutations -12A, -2A and +1T resembled the canonical sigma 70 promoter sequences. The +10A promoter activity is also dependent upon the sigma 70 holoenzyme but can not be readily assigned to a specific promoter sequence. IMAGES: